2013
DOI: 10.3402/tellusb.v65i0.19971
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a method for the objective differentiation of fog life cycle phases

Abstract: A B S T R A C T An objective classification of radiation fog in distinct evolutionary stages during its life cycle based on reliable criteria is essential for various applications, for example for numerical fog modelling and fog forecasting. However, there have been Á up to now Á merely qualitative approaches for the distinction of different evolutionary stages in radiation fog. Measurements of the microphysical fog properties with an optical particle counter obtained from droplet measurement technologies toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The range of dry activation diameters observed in this study overlaps with the range of typical D act values reported in other fog studies (∼ 300 to ∼ 500 nm; e.g., Noone et al, 1992a;Ming and Russell, 2004). However, the dry activation diameters observed in the fog are considerably larger than those observed and/or inferred within stratus or cumulus clouds (e.g., Ditas et al, 2012;Hammer et al, 2014;Hudson and Rogers, 1986;Krüger et al, 2014;McFiggans et al, 2006) due to the lower SS peak encountered in fog.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The range of dry activation diameters observed in this study overlaps with the range of typical D act values reported in other fog studies (∼ 300 to ∼ 500 nm; e.g., Noone et al, 1992a;Ming and Russell, 2004). However, the dry activation diameters observed in the fog are considerably larger than those observed and/or inferred within stratus or cumulus clouds (e.g., Ditas et al, 2012;Hammer et al, 2014;Hudson and Rogers, 1986;Krüger et al, 2014;McFiggans et al, 2006) due to the lower SS peak encountered in fog.…”
supporting
confidence: 82%
“…Cloud condensation nuclei (CCN) activity can be defined by the particles' critical supersaturation (SS crit ), that is, the lowest supersaturation at which the particles can activate to a fog or cloud droplet. The critical supersaturation depends on the size and chemical composition of the particle (McFiggans et al, 2006). Cooling of an air parcel to temperatures below its dew point will result in the formation of a cloud or fog, and those particles with a critical supersaturation below the peak supersaturation in the cloud are activated to form cloud droplets.…”
mentioning
confidence: 99%
“…This time difference does not exist between Aqua MODIS products and CloudSat because they are delayed by just 1 min in the A-train constellation [38]. It should be kept in mind that because cloud development is a highly dynamic process, even small time differences can be critical and of great importance for considerable oscillation in the microphysical properties of LST [39]. Second, the CloudSat and MYD06 products are calculated using vertical atmospheric profiles, whereas the case-adapted CAPCOM retrievals from JAMI and MODIS use real-time radiosonde data in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it would be difficult to relate the differing Z-LWC relationship directly to the high temporal DSD dynamics during fog development. By using the derived MGD parameters, the comparison with other studies, e.g., Maier et al [4], Harris [40], Tampieri and Tomasi [48], Tomasi and Tampieri [49] and Maier et al [30] is facilitated. Nevertheless, the difference between both procedures should be investigated in future studies, using more continuous DSD measurements during different radiation fog events.…”
Section: Discussionmentioning
confidence: 99%
“…While in some cases the fog dissipated due to evaporation, in other cases, it rose from the ground to form low stratus layers. The fog events were classified into three life cycle stages-"formation", "mature fog" and "dissipation"-by applying the breakpoint analysis presented in Maier et al [30] to the 2-m visibility data. The method is based on a double sum curve analysis and consists of three steps: First, a Mann-Whitney U-test [31] is conducted to find the most possible points in the time series where changes occurred.…”
Section: Fog Events and Synoptic Weathermentioning
confidence: 99%